Ultimate weird but true 2. (Washington, D.C. : National Geographic Society, 2013)
Presents facts, brief stories, photos, and illustrations showing that fact can be as weird as fiction.
Extreme weirdness -- This way up -- What's your number? -- Over the top -- It's only natural -- That's creepy! -- What's the deal? -- Eye wonder -- Wild world.
OSLIS\Gale Nat Geo eBooks(2/2/23).
"1,000 wild & wacky facts & photos!"--Cover.
Includes index.
Description based on print version record.
Keywords: Curiosities and wonders -- Juvenile literature; Curiosities and wonders; Curiosities and wonders; Electronic books- OSLIS; Juvenile works; Electronic books